Estudo da dinâmica costeira da região da foz do rio Piranhas-Açu para geração de mapas de sensibilidade do litoral ao derramamento de óleo - Mafra, Liliane Cristina de Albuquerque (2005)
The study area is located in the northern coast of Rio Grande do Norte State comprising the mouth of Açu-Piranhas river including the cities of Porto do Mangue e Areia Branca. The local geological setting comprises Cretaceous, Tertiary and Quaternary geological units of the Potiguar Basin. One is about a region of high morphologic instability due to action of the rigorous dynamic coastal processes, beyond the intense human activities mainly for the performance of the petroliferous industry, salt farms and tanks of shrimp industry.For the accomplishment of this work Landsat 5 TM and Landsat 7 ETM + from four distinct dates were used as cartographic base, in which one applied techniques of digital processing to elaborate thematic maps of the existing natural resources to support the geologic and geomorphologic characterization and the soil and landuse maps. The strategy applied was the interpretation of multitemporal images from aerial and orbital remote sensors alIied to the terrain truth recognition, integrated through a Geographic Information System. These activities had alIowed the production of Sensitivity Maps of the Coast to Oil Spilling for the area, on the basis of the Coastal Sensibility Index. Taking into account the seasons were created maps to distinct datas: July 2003 represents the winter months that presented a sensibility lower when compared with the month of December 2003. For the summer months greater sensitivity is due to the hydrodynamic data that suggest a lesser capacity of natural cleanness of the oil and its derivatives in spilling case.These outcomes are an important and useful database to support an assessment to a risk situation and to taking decision in the face of an environmental disaster with oil spilling in coastal area, alIowing a complete visualization of the area and identifying all portions in the area with thei environmental units and respective Coastal Sensibility Index.